School Refusal or Truancy? A Qualitative Study of Misconceptions Among School Personnel About Absenteeism of Children From Immigrant Families - Martin, Robin; Benoit, Jean Pierre; Moro, Marie Rose; Benoit, Laelia (Frontiers in Psychiatry, 2020)
Background: School refusal is a form of school attendance problem (SAP) distinct from truancy, school withdrawal, and school exclusion; it requires specific mental health care. Schools' identification and referral to care of school refusers depends on school personnel's interpretation of the reasons for absences. Because cultural factors can induce misunderstanding of the young people's behavior and of their parents’ attitudes toward school attendance, school personnel can have difficulty understanding these reasons for children with transcultural backgrounds (migrants or children of migrants). The aim of this study was to explore the experiences and opinions of school personnel, mainly teachers, related to school refusal among these students. Methods: Grounded theory methodology was used to conduct 52 qualitative interviews of school personnel in two regions of France. Their daily practices with students presenting with school refusal were addressed in general (i.e., in response to absence of all youth) and in transcultural contexts (i.e., absence of migrant children or children of migrants). This study analyzed the interviews of the 30 participants who reported working with students from transcultural backgrounds. Results: Many school personnel reported experiencing difficulties, ambivalence, and destabilizing feelings in situations involving immigrant families whose school culture differed from their own. Talking about culture appeared to be taboo for most participants. These situations challenged the participants' usual strategies and forced them to devise new ones to deal with these young people and their families. Although some personnel were at risk of developing exclusionary attitudes, others dealt with school refusal with both commitment and creativity. Conclusion: The tensions experienced by these participants reveal contradictions between the French universalist ideology and the reality of daily life in schools becoming increasingly multicultural. School personnel’s attitudes toward children with transcultural backgrounds presenting with school refusal can affect children's access to care and shape social inequalities. Further research should develop, implement, and assess interventions including transcultural training of school personnel, improved use of interpreters at school for migrant families, and the addition of a transcultural dimension to SAP assessment scales, especially for school refusal.